2020
DOI: 10.1042/bsr20191188
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms as non-modifiable susceptibility factors to laryngeal cancer

Abstract: Laryngeal squamous cell carcinoma (LSCC) is a highly disabling disease to the patient, affecting speech, swallowing and respiratory skills. Smoking and alcohol abuse are principal risk factors linked to this disease. Genetic factors can be involved in carcinogenesis by controlling the cell cycle, cell survival, angiogenesis, and invasiveness. Single nucleotide polymorphisms (SNPs) involving specific genes could modulate the risk of LSCC related to known carcinogens by modifying cellular responses, but not all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Previous studies have also reported an association of TP53 R72 SNPs with laryngeal cancer [51]. In yet another recent study, Escalante et al suggested that TP53 R72 SNPs may be a risk factor for the pathogenesis of laryngeal cancer [52]. In addition, in the upper gastrointestinal tract, an increased risk of esophageal SCC has been associated with TP53 R72 SNPs [53], as also suggested regarding lung and breast cancer in a South Asian population [54].…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have also reported an association of TP53 R72 SNPs with laryngeal cancer [51]. In yet another recent study, Escalante et al suggested that TP53 R72 SNPs may be a risk factor for the pathogenesis of laryngeal cancer [52]. In addition, in the upper gastrointestinal tract, an increased risk of esophageal SCC has been associated with TP53 R72 SNPs [53], as also suggested regarding lung and breast cancer in a South Asian population [54].…”
Section: Discussionmentioning
confidence: 81%
“…but disagree with, Sourvinos et al reporting that the Arg72Arg TP53 genotype may increase the incidence of laryngeal carcinoma and with Escalante et al how reported that C alle have an increased risk of laryngeal carcinoma. [20][21][22][23] Saleem et al in their study on oral squamous cell carcinoma that the homozygous change GG was more frequent (48.07%) than heterozygous GC (43.46%) or homozygous CC (8.47%) in the affected patient. 24 These differences in the impact of the Arg72Pro TP53 gene SNP on laryngeal and another carcinoma can be attributed to genetic heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Among the genetic factors studied are the presence of genes responsible for the production of certain proteins and enzymes and their polymorphisms [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%